A conductive paste for carbon-coated current collector, a preparation method thereof and a lithium ion battery
Patent Information
- Application Number
- CN202510585549.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-07
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-05-07
AI Technical Summary
Existing carbon-coated aluminum foils have residual oil stains during the preparation process, which causes the conductive paste to be incompatible with the aluminum foil surface, resulting in incomplete coating and affecting battery performance and service life.
Introducing multifunctional compounds containing amino, fluorine, and siloxane substituents into conductive pastes enhances the bonding force between the current collector and the active material through hydrogen and covalent bonds, reduces the coefficient of friction and surface energy, improves interfacial properties, and promotes spreading.
It significantly reduces foil leakage rate, improves electrode peeling force and the bonding force between active material and current collector, optimizes the coating performance of conductive paste, and enhances battery performance and lifespan.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a conductive slurry for carbon-coated current collectors, its preparation method, and a lithium-ion battery. Background Technology
[0002] With the advancement of lithium-ion battery technology, the positive electrode current collector of lithium-ion batteries includes, but is not limited to, ordinary aluminum foil. Carbon-coated aluminum foil has also been gradually applied in recent years, especially in lithium iron phosphate batteries. Carbon-coated aluminum foil can effectively improve the adhesion between the active material and the current collector, reduce the internal resistance of the battery, reduce polarization, and improve battery life and consistency. Therefore, it is particularly important to prepare high-performance carbon-coated aluminum foil. However, the aluminum foil in carbon-coated aluminum foil requires a large amount of rolling oil in the preparation process. This rolling oil cannot be completely removed in the final stage of aluminum foil production, resulting in oil stains remaining on the aluminum foil surface. Since most conductive pastes are water-based, they are incompatible with the oil stains on the aluminum foil surface. The paste is not easy to spread on the aluminum foil, and a large number of missed coatings will occur during coating, affecting the appearance and use of the carbon-coated aluminum foil, increasing the internal resistance of the battery, and affecting the battery life.
[0003] To this end, researchers have made improvements. For example, existing technologies disclose a carbon-coated current collector and its preparation method and application. The preparation method includes the following steps: (1) pre-treating and dispersing conductive carbon material: mixing conductive carbon material with deionized water and a dispersant, and then homogenizing to obtain a conductive carbon material premix; (2) mixing the conductive carbon material premix with deionized water, a binder, a wetting and dispersing agent, and lithium carbonate, and dispersing to obtain a conductive slurry; (3) coating the conductive slurry obtained in step (2) onto the surface of the current collector and baking to obtain the carbon-coated current collector. The wetting and dispersing agent includes any one or a combination of at least two of n-pentanol, ethanol, methanol, isopropanol, or sodium dodecylbenzenesulfonate. Existing technologies also provide a carbon-coated current collector and its preparation method and application. The carbon-coated current collector includes a current collector substrate and a carbon coating layer on at least one side of the current collector substrate; the carbon coating layer includes a conductive agent, a binder, and a crosslinking agent; the binder includes polyacrylic acid polymers and polystyrene microspheres. Existing technology also discloses a lithium-ion battery negative electrode sheet, which consists of a carbon-coated current collector and an active layer coated on the surface of the carbon-coated current collector. The carbon-coated current collector consists of a copper foil and a carbon layer coated on the surface of the copper foil. The active layer is made of an active material, a first binder, and a first conductive agent, and the carbon layer is made of a second binder and a second conductive agent. Although the above-mentioned existing technology can improve the phenomenon of slurry leakage and enhance the adhesion between the active material and the current collector to a certain extent, the effect is not significant and needs to be optimized.
[0004] Therefore, how to significantly improve the spreading of conductive paste on foil, reduce foil leakage rate, and significantly enhance the bonding force between active material and current collector, and improve electrode peeling force, is a hot research topic that urgently needs to be studied. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a conductive paste for carbon-coated current collectors, its preparation method, and a lithium-ion battery. The present invention introduces a multifunctional compound as shown in Formula I into the conductive paste. This multifunctional compound contains amino, fluorine substituents, and silicon oxide substituents. The amino group possesses a certain polarity and basicity, enabling it to form hydrogen bonds with the surface of the active material, thereby enhancing the bonding force between the current collector and the active material and improving the electrode peeling force. The silicon oxide substituents exhibit good flexibility and low surface energy, forming an interface layer with good affinity with the active material surface in the conductive paste. Furthermore, they reduce the coefficient of friction of the foil surface, allowing the conductive paste to spread better on the foil, thus significantly reducing the foil leakage rate. The fluorine substituents significantly improve the interfacial properties between the conductive paste and the foil surface, facilitating the wetting process. Their low surface energy also aids in the spreading of the conductive paste on the foil surface, further greatly reducing the foil leakage rate.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0008] The humectant includes a multifunctional compound as shown in Formula I:
[0009]
[0010] In this case, R1 is a fluorine substituent and R2 is a silicon-oxygen substituent.
[0011] This invention introduces a multifunctional compound as shown in Formula I into a conductive paste. This multifunctional compound contains amino, fluorine substituents, and siloxane substituents. The amino group has a certain polarity and basicity, which can interact with the surface of the active material to form hydrogen bonds, thereby enhancing the bonding force between the current collector and the active material and improving the electrode peeling force. The siloxane substituent has good flexibility and low surface energy, which can form an interface layer with good affinity with the surface of the active material in the conductive paste. It can also reduce the coefficient of friction of the foil surface, allowing the conductive paste to spread better on the foil, thereby greatly reducing the foil leakage rate. The fluorine substituent can significantly improve the interface properties between the conductive paste and the foil surface, which is beneficial to the wetting process. It also has a low surface energy, which helps the conductive paste spread on the foil surface, thereby greatly reducing the foil leakage rate.
[0012] In this invention, amino, fluorine, and siloxane substituents work synergistically. The amino group and the siloxane group form a dual bond through hydrogen and covalent bonds, significantly improving the adhesion between the conductive paste and the foil. The fluorine substituents reduce the surface tension gradient and, combined with the low viscosity of the siloxane chains, significantly improve the uniformity of the conductive paste coating thickness. Therefore, the synergistic effect of these three components effectively regulates the surface tension and viscosity of the conductive paste, greatly improving its spreading effect on the foil surface, thereby significantly reducing foil leakage. Furthermore, it also significantly enhances the peel strength of the electrode sheet.
[0013] Preferably, the fluorine substituent is selected from any one of fluorine atom, fluorinated alkyl, fluorinated alkenyl, fluorinated alkynyl, fluorinated alkoxy, fluorinated acyl or fluorinated aryl.
[0014] Preferably, the siloxane substituent includes any one of methoxysilyl, ethoxysilyl, trimethylsiloxy, phenylsiloxy, or fluorinated siloxy.
[0015] Preferably, the multifunctional compound is selected from at least one of the following compounds;
[0016]
[0017] In this invention, The CAS number is 660449-55-8; The CAS number is 2169267-73-4; The CAS number is 205700-47-6.
[0018] Preferably, the water-based adhesive includes any one or a combination of at least two of the following: polyacrylic acid adhesive, acrylate adhesive, acrylamide adhesive, polyurethane adhesive, and silane coupling agent adhesive.
[0019] In this invention, the water-based adhesive has the following functions: a binder, which helps to bond the components of the conductive slurry together and firmly bond the slurry to the foil; a dispersant, which makes the carbon material uniformly dispersed in the slurry system; a rheology modifier, which can adjust the rheological properties of the conductive slurry to ensure that the slurry has good workability; a conductive auxiliary agent, which has the auxiliary effect of improving the overall conductivity of the conductive slurry; and a protective agent, which has the function of protecting the carbon material from the influence of the external environment and improving the stability and service life of the slurry.
[0020] Preferably, the carbon material includes any one or a combination of at least two of conductive carbon black, conductive graphite, carbon nanotubes, graphene, and carbon fiber.
[0021] Preferably, the mass ratio of the wetting agent, the aqueous adhesive, and the carbon material is (1-5):(60-80):(10-30), wherein the range of the wetting agent "1-5" can be, for example, 1, 2, 3, 4, or 5, the range of the aqueous adhesive "60-80" can be, for example, 60, 65, 70, 75, or 80, and the range of the carbon material "10-30" can be, for example, 10, 15, 20, 25, or 30.
[0022] In this invention, if the mass ratio of the humectant to the carbon material is too small, it will not be conducive to the uniform dispersion of the carbon material and the spreading effect of the slurry will be poor, which will not be conducive to reducing the foil leakage rate; if the mass ratio of the humectant to the carbon material is too large, it will not be conducive to improving the adhesion of the conductive slurry.
[0023] In this invention, the appropriate amount of water-based adhesive, humectant, and carbon material work synergistically to help improve the dispersibility of the conductive paste, enhance the adhesion of the carbon material, reduce the contact resistance between the carbon material and the foil, optimize the coating performance of the conductive paste, and make it easier to spread the conductive material evenly on the surface of the foil.
[0024] Preferably, based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2-0.8%, for example, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%, etc.
[0025] In this invention, a suitable wetting agent helps to fully enhance the bonding force between the foil and the active material, while also fully adjusting the wettability of the conductive paste, so that the conductive paste can be better spread on the foil and reduce the foil leakage rate.
[0026] Preferably, the solvent includes water.
[0027] In a second aspect, the present invention provides a method for preparing a conductive paste for carbon-coated current collectors as described in the first aspect, the method comprising the following steps:
[0028] The wetting agent, aqueous adhesive, carbon material, and solvent are mixed to obtain the conductive paste for carbon-coated current collectors.
[0029] Preferably, the mixing method includes:
[0030] (a) The wetting agent and the solvent are first mixed to obtain a first dispersion; the first dispersion and the aqueous adhesive are second mixed to obtain a second dispersion.
[0031] (b) Mix the second dispersion with the carbon material.
[0032] The mixing method provided by this invention can further improve the mixing effect, making the components more uniformly mixed and the dispersion effect better.
[0033] Preferably, in step (a), the first mixing and the second mixing processes are each independently and sequentially subjected to vacuum stirring and dispersion.
[0034] In this invention, stirring in a vacuum environment effectively removes air and other volatile gases from the slurry, allowing the materials to fully contact and mix in a gas-free environment. The components are more evenly distributed under stirring, contributing to the formation of a stable and consistent conductive slurry. Furthermore, the vacuum environment reduces contact between oxygen and the materials, lowering the risk of oxidation and protecting the material's properties.
[0035] In this invention, the dispersion process further refines and uniformly disperses carbon materials and other particles in the slurry. This dispersion process also ensures that the components in the slurry form a stable suspension system, guaranteeing the stability of the conductive slurry during storage and use. Furthermore, the well-dispersed conductive slurry exhibits better rheological properties and coating performance, which helps reduce foil leakage rate.
[0036] Preferably, the vacuum stirring speed is 150-350 rpm, for example, it can be 150 rpm, 200 rpm, 250 rpm, 300 rpm or 350 rpm.
[0037] In this invention, a suitable vacuum stirring rate allows the carbon material, solvent, aqueous adhesive, and wetting agent to fully contact and mix in a vacuum environment, avoiding localized uneven mixing or agglomeration caused by over-stirring. It also helps bubbles escape quickly from the slurry, preventing damage to the material structure and performance due to excessive stirring rate.
[0038] Preferably, the dispersion rate is 500-700 rpm, for example, it can be 500 rpm, 550 rpm, 600 rpm, 650 rpm or 700 rpm.
[0039] In this invention, a suitable dispersion rate can provide sufficient shear and impact forces to break up agglomerated particles, distributing them uniformly in the slurry as individual particles or small aggregates. This improves particle dispersion and thus enhances the conductivity and stability of the conductive slurry. Simultaneously, while achieving good dispersion, maintaining appropriate particle size and surface properties is beneficial for subsequent processing and applications, and reduces foil leakage.
[0040] Preferably, the dispersion time is 30-50 minutes, for example, it can be 30 minutes, 35 minutes, 40 minutes, 45 minutes or 50 minutes.
[0041] Preferably, the mixing method in step (b) includes:
[0042] The carbon material is added to the second dispersion in multiple batches for mixing.
[0043] In this invention, the method of adding carbon material in multiple stages helps to disperse it more fully in the solution. Compared with adding a large amount of carbon material at once, adding it in stages allows the carbon material more time to fully contact and interact with the wetting agents and water-based adhesives in the solution, reducing agglomeration and thus improving the uniformity of carbon material dispersion in the solution. Secondly, it helps to optimize the mixing effect, improve the stability and rheological properties of the slurry, making it more suitable for subsequent coating and other processes, and reducing foil leakage rate.
[0044] It should be noted that the present invention does not limit the number of times, as long as it is greater than or equal to 2 times, such as 2 times, 3 times, 4 times or 5 times, etc.
[0045] Preferably, during the process of adding the carbon material in multiple stages, the material is stirred and dispersed after each addition.
[0046] Preferably, the stirring rate is 150-300 rpm, for example, it can be 150 rpm, 200 rpm, 250 rpm, 300 rpm or 350 rpm.
[0047] Preferably, the dispersion rate is 500-700 rpm, for example, it can be 500 rpm, 550 rpm, 600 rpm, 650 rpm or 700 rpm.
[0048] Preferably, the dispersion time is 30-50 minutes, for example, it can be 30 minutes, 35 minutes, 40 minutes, 45 minutes or 50 minutes.
[0049] Thirdly, the present invention provides a carbon-coated current collector, the carbon-coated current collector comprising a foil and a conductive coating disposed on the surface of the foil, the conductive coating being prepared by a conductive paste for the carbon-coated current collector as described in the first aspect, or the conductive coating being prepared by a conductive paste prepared by the preparation method described in the second aspect.
[0050] It should be noted that the present invention does not limit the type of foil material; for example, it can be aluminum foil.
[0051] Preferably, the thickness of the conductive coating is 0.5-1 μm, for example, it can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm.
[0052] The present invention provides a conductive coating of suitable thickness that not only helps to improve the bonding force between the foil and the active material, but also has excellent spreading effect and greatly reduces the foil leakage rate.
[0053] Fourthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a carbon-coated current collector as described in the third aspect.
[0054] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] This invention introduces a multifunctional compound as shown in Formula I into a conductive paste. This multifunctional compound contains amino, fluorine substituents, and siloxane substituents. The amino group has a certain polarity and basicity, which can interact with the surface of the active material to form hydrogen bonds, thereby enhancing the bonding force between the current collector and the active material and improving the electrode peeling force. The siloxane substituent has good flexibility and low surface energy, which can form an interface layer with good affinity with the surface of the active material in the conductive paste. It can also reduce the coefficient of friction of the foil surface, allowing the conductive paste to spread better on the foil, thereby greatly reducing the foil leakage rate. The fluorine substituent can significantly improve the interface properties between the conductive paste and the foil surface, which is beneficial to the wetting process. It also has a low surface energy, which helps the conductive paste spread on the foil surface, thereby greatly reducing the foil leakage rate. Detailed Implementation
[0057] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0058] Example 1
[0059] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0060] The humectant is a multifunctional compound as shown below:
[0061]
[0062] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:60:10; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2%; the solvent is water.
[0063] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0064] (1) Mix 1g of wetting agent and 429g of water in a mixer to obtain a first dispersion; mix the first dispersion with 60g of water-based adhesive to obtain a second dispersion.
[0065] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0066] (2) Add 10g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0067] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0068] Example 2
[0069] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0070] The wetting agent is a multifunctional compound as shown below:
[0071]
[0072] The water-based adhesive is an acrylic ester adhesive; the carbon material is conductive graphite; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:10; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2%; the solvent is water.
[0073] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0074] (1) Mix 1g of wetting agent and 419g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0075] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 150 rpm, the dispersion rate is 500 rpm, and the dispersion time is 50 min.
[0076] (2) Add 10g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0077] The stirring rate was 200 rpm, the dispersion rate was 500 rpm, and the dispersion time was 50 min.
[0078] Example 3
[0079] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0080] The wetting agent is a multifunctional compound as shown below:
[0081]
[0082] The aqueous adhesive is an acrylamide adhesive; the carbon material is carbon nanotubes; the mass ratio of the wetting agent, aqueous adhesive, and carbon material is 1:80:10; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2%; the solvent is water.
[0083] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0084] (1) Mix 1g of wetting agent and 409g of water in a mixer to obtain a first dispersion; mix the first dispersion with 80g of water-based adhesive to obtain a second dispersion.
[0085] In the process of mixing the first mixture and mixing the second mixture, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 350 rpm, the dispersion rate is 700 rpm, and the dispersion time is 30 min.
[0086] (2) Add 10g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0087] The stirring rate was 150 rpm, the dispersion rate was 700 rpm, and the dispersion time was 40 min.
[0088] Example 4
[0089] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0090] The wetting agent is a multifunctional compound as shown below:
[0091]
[0092] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:20; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2%; the solvent is water.
[0093] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0094] (1) Mix 1g of wetting agent and 409g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0095] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0096] (2) Add 20g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0097] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0098] Example 5
[0099] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0100] The wetting agent is a multifunctional compound as shown below:
[0101]
[0102] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:30; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2%; the solvent is water.
[0103] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0104] (1) Mix 1g of wetting agent and 399g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0105] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0106] (2) Add 30g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collector.
[0107] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0108] Example 6
[0109] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0110] The wetting agent is a multifunctional compound as shown below:
[0111]
[0112] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:90:10; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2%; the solvent is water.
[0113] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0114] (1) Mix 1g of wetting agent and 399g of water in a mixer to obtain a first dispersion; mix the first dispersion with 90g of water-based adhesive to obtain a second dispersion.
[0115] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0116] (2) Add 10g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0117] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0118] Example 7
[0119] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0120] The wetting agent is a multifunctional compound as shown below:
[0121]
[0122] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:90:40; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.2%; the solvent is water.
[0123] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0124] (1) Mix 1g of wetting agent and 369g of water in a mixer to obtain a first dispersion; mix the first dispersion with 90g of water-based adhesive to obtain a second dispersion.
[0125] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0126] (2) Add 40g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0127] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0128] Example 8
[0129] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0130] The wetting agent is a multifunctional compound as shown below:
[0131]
[0132] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:20; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.5%; the solvent is water.
[0133] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0134] (1) Mix 1g of wetting agent and 109g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0135] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0136] (2) Add 20g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0137] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0138] Example 9
[0139] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0140] The wetting agent is a multifunctional compound as shown below:
[0141]
[0142] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:20; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.8%; the solvent is water.
[0143] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0144] (1) Mix 1g of wetting agent and 34g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0145] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0146] (2) Add 20g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0147] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0148] Example 10
[0149] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0150] The wetting agent is a multifunctional compound as shown below:
[0151]
[0152] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, the water-based adhesive, and the carbon material is 1:70:20; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 1%; the solvent is water.
[0153] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0154] (1) Mix 1g of wetting agent and 9g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0155] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0156] (2) Add 20g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0157] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0158] Example 11
[0159] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0160] The wetting agent is a multifunctional compound as shown below:
[0161]
[0162] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:20; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.5%; the solvent is water.
[0163] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0164] (1) Mix 1g of wetting agent and 109g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0165] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0166] (2) Add 20g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0167] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0168] Example 12
[0169] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0170] The wetting agent is a multifunctional compound as shown below:
[0171]
[0172] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:20; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.5%; the solvent is water.
[0173] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0174] (1) Mix 1g of wetting agent and 109g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0175] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0176] (2) Add 20g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0177] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0178] Example 13
[0179] This embodiment provides a conductive paste for carbon-coated current collectors, the conductive paste comprising a wetting agent, an aqueous adhesive, a carbon material, and a solvent.
[0180] The wetting agent is a multifunctional compound as shown below:
[0181]
[0182] The water-based adhesive is a polyacrylic acid adhesive; the carbon material is conductive carbon black; the mass ratio of the wetting agent, water-based adhesive, and carbon material is 1:70:20; based on the mass of the conductive paste as 100%, the mass fraction of the wetting agent is 0.1%; the solvent is water.
[0183] This embodiment also provides a method for preparing the above-mentioned conductive paste for carbon-coated current collectors, the preparation method comprising the following steps:
[0184] (1) Mix 1g of wetting agent and 909g of water in a mixer to obtain a first dispersion; mix the first dispersion with 70g of water-based adhesive to obtain a second dispersion.
[0185] In the process of the first mixing and the second mixing, vacuum stirring and dispersion are carried out independently and sequentially. The vacuum stirring rate is 250 rpm, the dispersion rate is 600 rpm, and the dispersion time is 40 min.
[0186] (2) Add 20g of carbon material to the second dispersion in three portions, stirring and dispersing after each addition to obtain the conductive slurry for carbon-coated current collectors.
[0187] The stirring rate was 300 rpm, the dispersion rate was 600 rpm, and the dispersion time was 30 min.
[0188] Comparative Example 1
[0189] The difference between this comparative example and Example 8 is that the lubricant is replaced with an equal mass of isopropanol.
[0190] The remaining preparation methods and parameters are consistent with those in Example 8.
[0191] Comparative Example 2
[0192] The difference between this comparative example and Example 8 is that the wetting agent is replaced with the following multifunctional compound (CAS No.: 14791-78-7):
[0193]
[0194] The remaining preparation methods and parameters are consistent with those in Example 8.
[0195] Comparative Example 3
[0196] The difference between this comparative example and Example 8 is that the wetting agent is replaced with the following multifunctional compound (CAS No.: 113984-68-2):
[0197]
[0198] The remaining preparation methods and parameters are consistent with those in Example 8.
[0199] Comparative Example 4
[0200] The difference between this comparative example and Example 8 is that the wetting agent is replaced with the following multifunctional compound (CAS No.: 121942-75-4):
[0201]
[0202] The remaining preparation methods and parameters are consistent with those in Example 8.
[0203] Comparative Example 5
[0204] The difference between this comparative example and Example 8 is that the aqueous adhesive is replaced with an equal mass of water.
[0205] The remaining preparation methods and parameters are consistent with those in Example 8.
[0206] Performance testing
[0207] 1. The conductive pastes provided in the above embodiments and comparative examples were tested on aluminum foil for contact angle.
[0208] 2. The conductive pastes provided in the above embodiments and comparative examples are coated onto aluminum foil, dried, and then inspected using a coordinate measuring machine. The number of foil leakage points is recorded at a magnification of 2W.
[0209] 3. The conductive pastes provided in the above embodiments and comparative examples are coated onto aluminum foil to form negative electrode sheets. The resulting negative electrode sheets are then subjected to peel force testing using a universal tensile testing machine.
[0210] The test results are shown in Table 1.
[0211] Table 1
[0212]
[0213]
[0214] analyze:
[0215] As shown in Table 1, comparing Examples 1, 2, 3, 4, 5, 6, and 7, the optimal performance is achieved when the ratio of wetting agent: aqueous adhesive: carbon material is 1:70:20. Comparing Examples 4, 8, 9, 10, and 13, the optimal performance is achieved when the wetting agent content is 0.5%. Comparing Examples 8, 11, 12, Comparative Examples 1, 2, 3, and 4, the optimal performance is achieved when the wetting agent simultaneously contains amino, siloxane, and fluorine substituents. Comparing Examples 8 and 5, the aqueous adhesive plays a crucial role in improving the wettability of the conductive paste, reducing foil leakage, and increasing the peel strength of the electrode. In summary, Example 8 of the present invention is the best and can significantly improve electrode performance.
[0216] It should be noted that the present invention is illustrated through the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A conductive paste for carbon-coated current collectors, characterized in that, The conductive paste includes a wetting agent, an aqueous adhesive, a carbon material, and a solvent; The humectant includes a multifunctional compound as shown in Formula I: Equation I; In this case, R1 is a fluorine substituent and R2 is a silicon-oxygen substituent.
2. The conductive paste for carbon-coated current collectors according to claim 1, characterized in that, The fluorine substituent is selected from any one of fluorine atom, fluorinated alkyl, fluorinated alkenyl, fluorinated alkynyl, fluorinated alkoxy, fluorinated acyl or fluorinated aryl.
3. The conductive paste for carbon-coated current collectors according to claim 1, characterized in that, The siloxane substituent includes any one of methoxysilyl, ethoxysilyl, trimethylsiloxy, phenylsiloxy, or fluorinated siloxy.
4. The conductive paste for carbon-coated current collectors according to claim 1, characterized in that, The multifunctional compound is selected from at least one of the following compounds; ; ; 。 5. The conductive paste for carbon-coated current collectors according to claim 1, characterized in that, The aqueous adhesive includes any one or a combination of at least two of the following: polyacrylic acid adhesive, acrylate adhesive, acrylamide adhesive, polyurethane adhesive, and silane coupling agent adhesive.
6. The conductive paste for carbon-coated current collectors according to claim 1, characterized in that, The carbon material includes any one or a combination of at least two of the following: conductive carbon black, conductive graphite, carbon nanotubes, graphene, and carbon fiber.
7. The conductive paste for carbon-coated current collectors according to claim 1, characterized in that, The mass ratio of the wetting agent, the aqueous adhesive and the carbon material is (1-5):(60-80):(10-30).
8. The conductive paste for carbon-coated current collectors according to claim 1, characterized in that, Based on the mass of the conductive paste being 100%, the mass fraction of the wetting agent is 0.2-0.8%.
9. A method for preparing a conductive paste for carbon-coated current collectors as described in any one of claims 1-8, characterized in that, The preparation method includes the following steps: The wetting agent, water-based adhesive, carbon material, and solvent are mixed to obtain the conductive paste for carbon-coated current collectors.
10. The preparation method according to claim 9, characterized in that, The mixing method includes: (a) The wetting agent and the solvent are first mixed to obtain a first dispersion; the first dispersion and the aqueous adhesive are second mixed to obtain a second dispersion; (b) Mix the second dispersion with the carbon material.
11. The preparation method according to claim 10, characterized in that, In step (a), vacuum stirring and dispersion are performed independently and sequentially during the first mixing and the second mixing processes.
12. The preparation method according to claim 11, characterized in that, The vacuum stirring speed is 150-350 rpm.
13. The preparation method according to claim 11, characterized in that, The dispersion rate is 500-700 rpm.
14. The preparation method according to claim 11, characterized in that, The dispersion time is 30-50 minutes.
15. The preparation method according to claim 10, characterized in that, The mixing method described in step (b) includes: The carbon material is added to the second dispersion in multiple batches for mixing.
16. The preparation method according to claim 10, characterized in that, During the process of adding the carbon material in multiple stages, stirring and dispersion were performed after each addition.
17. The preparation method according to claim 16, characterized in that, The stirring speed is 150-300 rpm.
18. The preparation method according to claim 16, characterized in that, The dispersion rate is 500-700 rpm.
19. The preparation method according to claim 16, characterized in that, The dispersion time is 30-50 minutes.
20. A carbon-coated current collector, characterized in that, The carbon-coated current collector includes a foil and a conductive coating disposed on the surface of the foil. The conductive coating is prepared by the conductive paste for the carbon-coated current collector according to any one of claims 1-8, or the conductive coating is prepared by the conductive paste prepared by the preparation method according to any one of claims 9-19.
21. A lithium-ion battery, characterized in that, The lithium-ion battery includes the carbon-coated current collector as described in claim 20.
Citation Information
Patent Citations
Production of aromatic carboxamides by palladium-catalyzed carbonylation reactions
CN115315419A
Electrolyte, secondary battery, and electric device
CN116470141A
